Heritage, memory & identity - Anheier, Helmut K.; Isar, Yudhishthir Raj (The cultures and globalization series, 2011)
"Heritage, memory, and identity are closely connected keywords of our time, each endowed with considerable rhetorical power. Different human groups define certain objects and practices as 'heritage'; they envision heritage to reflect some form of collective memory, either lived or imagined; and they combine both to construct cultural identities. Today, the three terms raise conjoined issues of practice, policy and politics in an increasingly globalized world. Bringing together a truly global range of scholars, this volume explores heritage, memory, and identity through a diverse set of subjects, including heritage sites, practices of memorialization, museums, sites of contestation, and human rights."--Publisher description